Thromboembolic Occlusion of Left Bracheal artery Protein-C and Protein-S Deficiency - A Case Report (Cardiovascular Journal, 2010)
Protein-C and Protein-S deficiency states are responsible for 3-5% (Protein-C) and 2-3% (Protein-S) of patients with venous thrombosis. Some cases of arterial thrombosis have been reported. It occurs twice as often in female as in males. A 50 years old lady presented with acute severe pain in the left upper limb for 2 days. On investigation she was diagnosed as a case of bracheal artery thrombosis with Protein-C & Protein-S deficiency. Bracheal thromboembolectomy was done and discharge her with life long warfarin therapy. In one year follow up the patient had no untoward event and INR done every month and warfarin is adjusted. Keywords: Arterial thromboembolism; Protein-C and Protein-S deficiency. DOI: 10.3329/cardio.v3i1.6433Cardiovasc. j. 2010; 3(1): 92-93